Economic growth and NOx emissions in the post-communist country - Lešáková, Petra (Varazdin Development and Entrepreneurship Agency, 2019)
Due to the newly available consistent historical dataset, this paper will contribute to the debate on the link between economic growth and the environmental burden in case of the postcommunist country of the Czech Republic. More specifically, the analysis will test environmental Kuznets curve (EKC) for NOX emissions between 1980 and 2015. However, modelling on long-term data did only prove decreasing phase of EKC but did not show increasing phase. Therefore, it can be assumed that breaking point occurred earlier than in the monitored period. However, political and economic transformation processes in the 1990s had significant impact on the decreasing burden on the environment in terms of NOX
Hospodářský růst a emise NOx v postkomunistické zemi
Keywords: Economic Development; Environmental Burden; Environmental Kuznets Curve; Decoupling; NOX Emissions; Ekonomický vývoj; Environmentální zátěž; Environmentální Kuznetsova křivka; Deocupling; Emise NOx